Inter-subjective influence in contemporary society: socio-psychological aspects - M. .. Yuzhanin; N. S. Yuzhanina (Путеводитель предпринимателя)
In the presented article socio -psychological mechanisms and basic principles of intersubjective mutual influence in a context of contemporary social reality are considered, and also possible ways of overcoming the arising manipulations are designated.